Serum Magnesium Level in Migraineurs Versus Non Migraineurs (Medical Forum Monthly, 2024)
Objective: The objective is to observe relationship between low serum magnesium level and Migraine.Study Design: Prospective Observational.Place and Duration of Study: This study was conducted in Dow University Hospital, Dow University of Health Sciences, Karachi from 1st January 2013 to 31st December 2014.Materials and Methods: One hundred and fifty patients attending the medical and Neurology OPD at Dow University Hospital were included in study. They were diagnosed according to International Headache Society (IHS) criteria for migraine headache.Results:150 patients were enrolled in study 49 (32.7%) were male and 101 (67.3%) were female patients mean age was 28 (±6.2) years , After excluding other causes migraine was diagnosed in 102 (68%) patients. Out of 102 patients 71 (69.7%) were have low serum magnesium level. In the remaining patients with non migrainous headache, only 6 patients (12.5%) have low serum magnesium level because of some other causes for example medications.Conclusion: Migraine is frequently associated with Serum low level of Magnesium compare to patient with non migrainous headache.